KAJIAN KELAYAKAN TEKNOLOGI USAHA TANI PADI SAWAH TADAH HUJAN DI MERAUKE PAPUA - Malik, Afrizal; Jamil, Andi (Universitas Sebelas Maret, 2008)
Research aims are to study economic eligibility of rain paddy wet rice field with innovation use of certifiable seed, fertilization recommendation and application and also apart to plant. The research apply farmer rice field farm at dry season 2005 in Semangga Java village, Semangga district, Merauke regency. Source of data use collected primary data by record keeping and PRA. Data analysis conducted descriptively qualitative and quantitative use parsial budget analysis, with economic parameter of R/C, MBCR, TIP and TIH continued with sensitivity analysis. The result of research shown (1) component appearance result of technological introduction rain paddy wet rice field is better than farmer pattern, (2) rice field paddy introduction technology yield productivity 5,7 ton/ha while farmer pattern only reach 3,2 ton/ha, (3) applying technological package of rain paddy wet rice field can give advantage addition equal to Rp 8.347.274/ha with MBCR value 6,65, (4) rice field paddy survival technology still can stay in a condition to make-up of input price 25% and degradation of shell of rice price 15%. For the succes of applying technological innovation, needed medium support produce close to development location rice field with price which reached to be accompanied continuity adjacent.